Comparison of Extracellular Metabolites and Antioxidant Activity of Different Strains of Wolfiporia hoelen (Fr.) Y.C. Dai &V. Papp - TAN Yun, SHEN Airong, SHEN Baoming, YU Jinxiu, LIU Lina, LI Sainan, TAN Zhuming (Shipin Kexue)
This study examined the differences in the extracellular metabolites and in vitro antioxidant activity of 8 strains of Wolfiporia hoelen (Fr.) Y.C. Dai &V. Papp and conducted their comprehensive evaluation using principal component analysis (PCA). To investigate the major antioxidant components of W. hoelen, widely targeted metabolomics was used to analyze the composition of extracellular flavonoids and phenolic compounds. The results showed that the contents of extracellular polysaccharides, total triterpenes and sterols were the highest in strain GTR1. The contents of extracellular flavonoids and phenolics were the highest in strain GTR2. The results of in vitro antioxidant tests showed that strains F5.78, GTR2 and XJ28 had the highest capacity to scavenge 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cation, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radicals, respectively. The results of correlation analysis showed that the contents of extracellular flavonoids was highly significantly positively correlated with the DPPH radical scavenging capacity and the contents of extracellular total phenols in W. hoelen (P < 0.01). Totally 55 flavonoids and 33 phenolic compounds were qualitatively detected using ultra-high performance liquid chromatography-mass spectrometry (UPLC-MS). The relative content of each component varied among different W. hoelen strains; the most abundant flavonoid was malonyldaidzin and the most abundant phenolic component was 3-formylsalicylic acid in W. hoelen strains FLA, FGD, FGZ, FHB, GTR1, XJ28 and F5.78. The most abundant flavonoid component in strain GTR2 was kaempferol-3-O-(6-galloyl)glucoside, which was highly significantly positively correlated with the DPPH radical scavenging capacity (P < 0.01). In this strain, the most abundant phenolic component was α-cyano-4-hydroxycinnamic acid, which was significantly positively correlated with the DPPH radical scavenging capacity (P < 0.05). PCA showed that GTR2 scored highest among the eight strains. In conclusion, this strain has a high content of extracellular bioactive ingredients and good antioxidant activity, making it a potential candidate for the development of antioxidant products.